Centro Gastronómico Cultural En El Municipio De San Agustín Como Fortalecimiento Del Turismo Y El Patrimonio Cultural En El Departamento Del Huila. - Pérez Losada, Anyi Lorena (Universidad Antonio Nariño, 2023)
The gastronomy in Huila has had a deeply rooted connotation through the different existing cultures, which have been characterized depending on the region, where in some places they have been used and considered elements of an immaterial nature for which the opportunity to appropriate this cultural element in our region due to the great tourist potential existing in the department of Huila. In this department there is the peculiarity of showing a number of very typical gastronomic cultures depending on the municipality where it is located, which have been appropriate since our ancestors, contributing to the entire population as well as social development, but which has not been considered an element primordial, causing the loss of the importance of the region. This thesis consists of developing an architectural project, Cultural Gastronomic Center in the municipality of San Agustín, whose purpose is to promote tourism and promote the dissemination, training and research of Huila gastronomy. In this way, it seeks to contribute to the consolidation of the department of Huila as an important and competitive gastronomic tourist destination worldwide.